An engineering approach to design of dextran microgels size fabricated by water/oil emulsification. (17th August 2016) - Salimi-Kenari, Hamed; Imani, Mohammad; Nodehi, Azizollah; Abedini, Hossein
Abstract: A correlation, based on fluid mechanics, has been investigated for the mean particle diameter of crosslinked dextran microgels (CDMs) prepared via a water/oil emulsification methodology conducted in a single-stirred vessel. To this end, non-dimensional correlations were developed to predict the mean particle size of CDMs as a function of Weber number, Reynolds number and viscosity number similar to ones introduced for liquid–liquid dispersions. Moreover, a Rosin–Rammler distribution function has been successfully applied to the microgel particle size distributions. The correlations were validated using experimentally obtained mean particle sizes for CDMs prepared at different stirring conditions. The validated correlation is especially applicable to medical and pharmaceutical applications where strict control on the mean particle size and size distribution of CDMs are extremely essential.